Elaboration of geotechnical charts applied to collapsible soils in urban areas using the Progressive Detailing Method - da Silveira, Paulo Edison Martins; Reis, Fábio Augusto Gomes Vieira [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Many works deal with the collapse of soils; however, few are focused on urban planning. The present paper presents procedures for the elaboration of geotechnical charts applied to collapsible soils in urban areas, discussing the influence of the work scale, geotechnical mapping procedures, and laboratory tests for the assessment of the phenomenon. The work sought criteria for the elaboration of geotechnical maps applied to collapsible soils in these areas, based on the method of progressive detailing, focusing on the main constraints to the occurrence of the process and the most appropriate geotechnical tests in each study stage. Herein, the results obtained for two stages of the referred method are presented, the general (1:50,000) and the semi-detail (1:25,000). In the first, the following procedures were performed: analysis of thematic cartographic documentation and bibliographic compilation; photointerpretation; field survey; conducting laboratory tests; analysis of geotechnical survey profiles; elaboration of a geotechnical chart (1:50,000) with the generation of geological-geotechnical units by multithematic analysis with crossing of declivity, hypsometric, geological, pedological, geotechnical, and laboratory data; and finally, these results were integrated to define susceptible zones the occurrence of these soils and the choice of the target area for the studies of the semidetail stage. In this stage, the following activities were carried out: complementary survey of this area, edometric tests to confirm the occurrence of the phenomenon, and the elaboration of a geotechnical chart (1:25,000). Based on the results obtained, the conclusion is that the progressive detailing methodology, with its different work scales, objectives and procedures, presents itself as an important tool in the elaboration of susceptibility charts to the phenomenon of soil collapse in urban areas, with the advantage of optimize financial, personal, and time resources.
Elaboração de cartas geotécnicas aplicadas a solos colapsíveis em áreas urbanas utilizando o método do detalhamento progressivo
Keywords: Collapse in urban areas; Geotechnical mapping; Soil collapsibility